RISK FACTORS ASSOCIATED TO Neospora caninum INFECTION IN DAIRY COWS IN PERNAMBUCO FATORES DE RISCOS ASSOCIADOS À INFECÇÃO POR Neospora caninum EM MATRIZES BOVINAS LEITEIRAS EM PERNAMBUCO - Silvana Suely de Assis Rabelo; José Wilton Pinheiro Junior; Rinaldo Aparecido Mota; Maria Ângela Ornelas Almeida; Maria Inês Santos Silva (Ciência Animal Brasileira, 2008)
The aim of the present work was to evaluate the risk factors associated to Neospora caninum in dairy cows in the state of Pernambuco. Were collected 469 blood samples originated from 20 different farms. Indirect Immunofluorescence (IFI) was the technique employed to detect N. caninum antibodies in the samples. During sample collection, epidemiological inquiring was performed. From the samples tested, 31.7% (163/469) showed a positive reaction to N. caninum, distributed among 17 (85%) of the properties studied. It was observed a significant association with all aspects related to hygienic-sanitary management such as veterinary assistance (p = 0.011); nutritional condition (p = 0.031); presence of wetlands (p < 0.001); manipulation of newborn calves (p < 0.001) and the fate of the cows had aborted (p = 0.004). Moreover, risk factors associated to reproductive disturb such as abortion history (p = 0.042) and abortions period (p = 0.014), were also observed. The findings described in this study characterize the first evidence of N. caninum infection in dairy cows in the state of Pernambuco, demonstrating the necessity of performing systematic diagnosis and monitoring of the cattle regarding their reproductive efficiency, in addition to the implementation of prophylactic and control measures. KEY WORDS: Cattle, epidemiologic aspects, indirect immunofluorescence, Neospora caninum. Objetivou-se com este trabalho avaliar os fatores de riscos associados à infecção pelo Neospora caninum em matrizes bovinas leiteiras no Estado de Pernambuco. Colheram-se 469 amostras de sangue, distribuídas em vinte propriedades. A técnica utilizada para detecção de anticorpos contra N. caninum foi a imunofluorescência indireta (IFI). Durante a colheita das amostras, aplicaram-se questionários investigativos. Das amostras testadas, 31,7% (163/469) foram reagentes para N. caninum, distribuídas em dezessete (85,0%) propriedades. Observou-se associação significativa com todos aqueles relacionados ao manejo higiênico-sanitário como assistência veterinária (p = 0,011); estado nutricional (p = 0,031); presença de instalações alagadiças (p < 0,001); manuseio do feto (p< 0,001); destino das vacas que abortaram (p = 0,004) e com alguns fatores relacionados aos distúrbios reprodutivos como histórico de aborto (p= 0,042) e época do aborto (p = 0,014). Esses achados registram a primeira ocorrência da infecção pelo N. caninum em matrizes bovinas leiteiras no Estado de Pernambuco, indicando-se a necessidade da realização do diagnóstico sistemático e monitoramento dos rebanhos quanto à eficiência reprodutiva, além da implantação de medidas de controle e profilaxia. PALAVRAS-CHAVES: Aspectos epidemiológicos, imunofluorescência indireta, bovinos, Neospora caninum.